IL17A and IL17RA gene polymorphisms in Fanconi anemia - Rafael Zancan MOBILE; Monalisa Castilho MENDES; Cleber MACHADO-SOUZA; Priscila de Mattos QUEIROZ; Carmem Maria Sales BONFIM; Cassius Carvalho TORRES-PEREIRA; Juliana Lucena SCHUSSEL (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Fanconi anemia is a rare autosomal recessive disease. In this disease, cytokine pathways can induce the bone marrow failure that is observed in individuals with Fanconi anemia. Interleukin IL-17 exhibits a protective effect in organisms because it induces neutrophil recruitment and shows a pathological role in several models of autoimmune diseases, periodontal disease, cancer, allograft rejection, and graft versus host disease. Polymorphisms in the IL17A and IL17RA genes were evaluated from DNA in saliva, comparing individuals with or without Fanconi anemia, using models of genotypic transmission (additive, dominant, and recessive). Polymorphisms in the IL17A and IL17RA genes (rs2241044 [C allele], rs879577 [C allele], rs9606615 [T allele], and rs2241043 [C allele]) were risk factors for developing Fanconi anemia. We also performed an analysis of gene markers with clinical variables in the Fanconi group. Polymorphisms in the IL17A gene (rs3819025 [A allele] and rs2275913 [G allele], respectively) were associated with an age of less than 20 years (p = 0.026; RP 0.65) and the female sex (p = 0.043; RP 0.88). The IL17RA gene was also associated with age and the presence of leukoplakia (a potentially malignant oral disorder). An age of less than 20 years was associated with rs917864 (T allele; p = 0.036; RP 0.67). The presence of leukoplakia was associated with rs17606615 (T allele; p = 0.042; RP 0.47). To our knowledge, this is the first study that associates IL17A and IL17RA gene polymorphisms with Fanconi anemia and examines rs2241044 polymorphisms in scientific literature thus far.